If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(4z + 2) = 3(87 + 4) Reorder the terms: 6(2 + 4z) = 3(87 + 4) (2 * 6 + 4z * 6) = 3(87 + 4) (12 + 24z) = 3(87 + 4) Combine like terms: 87 + 4 = 91 12 + 24z = 3(91) Multiply 3 * 91 12 + 24z = 273 Solving 12 + 24z = 273 Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-12' to each side of the equation. 12 + -12 + 24z = 273 + -12 Combine like terms: 12 + -12 = 0 0 + 24z = 273 + -12 24z = 273 + -12 Combine like terms: 273 + -12 = 261 24z = 261 Divide each side by '24'. z = 10.875 Simplifying z = 10.875
| 9.99+1.25*9= | | u/6+k=3u | | 50.00-6.00d=2 | | p=7-4y+y^2 | | (1/2)x+6=19 | | p=Y*Y-4*Y+7 | | 177=25p+27 | | 9.99+1.25*8= | | 1x/2+6=19 | | x=5.6+.4y | | 8(4y)+2y=50 | | y=5.6+.4x | | d/15=4 | | -x+3=2x+0 | | x/8+9=x/8 | | 4.43x+3.41y=50.10 | | y=33(4)-0.5 | | 10(h+1)=3(2h+4)-2(-2h+1) | | 9.99+1.25*7= | | y=33(2)-0.5 | | 24x+1=4 | | -2-(3/4x)=10 | | 9.99+1.25*6= | | 3x+6=-2x+41 | | 3r+18/12=4r-24/4 | | 9.99+1.25*5= | | 9=-3/5x | | 9.99+1.25*4= | | -7/4=p/28 | | 7/2+12=6+5/2 | | 7/2+12=6+5/2 | | 9.99+1.25*3= |